Optimizing Digital Marketing for Competitive MSMEs: Integration of E-Commerce and Social Media in Gorontalo - Deby Rita Karundeng; Mohamad Afan Suyanto (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Despite their substantial economic contribution, many MSMEs still struggle to optimize digital marketing, as their use of social media and e-commerce remains fragmented and limited, reducing competitiveness in wider markets. This study aims to examine the utilization of digital marketing among MSMEs in Gorontalo, focusing on the integration of e-commerce and social media. Using a mixed-methods approach, data were collected through surveys, focus group discussions, and in-depth interviews with MSMEs, government, and academics. Results show that while most MSMEs rely on Facebook and WhatsApp for promotion, their use of e-commerce platforms such as Shopee and Tokopedia remains limited due to high shipping costs, limited human resources, and weak content management strategies. Analytical findings highlight three key barriers: low digital readiness, lack of platform synergy, and structural challenges such as logistics costs. In response, this study proposes an integrative digital marketing model consisting of three components: digital readiness, strategic alignment, and platform synergy. The model has been preliminarily validated with MSME actors and is considered relevant and applicable. The findings contribute to designing policies, academic interventions, and practical strategies to enhance MSME competitiveness in the digital era.